Evaluating the impact of Internet provision on students' information-gathering strategies - Julia Meek; Marie Garnett; John Grattan (Association for Learning Technology, 1998)
Universities may invest millions of pounds in the provision of computer hardware without ever seriously considering the educational results such investment may deliver. Equally, academics may be committed to the use of IT in teaching and learning because it is expected of them (cf. Dearing, 1997), and rarely give serious consideration to the impact which the effective use of IT may have on student learning (Lauillard, 1993). The use of the WWW to deliver material in support of university teaching is still in its infancy, yet already two distinct approaches to its use can be seen. The first approach uses the WWW passively to deliver existing lecture notes in a technologically impressive and, perhaps more importantly, highly convenient fashion. The second approach attempts to shape the material delivered to maximize the teaching and learning potential of the WWW and to develop students' skills in the use of the medium. But which approach works more effectively? And how does one balance the needs of an academic community pressured by the Research Assessment Exercise with the need to develop effective teaching and learning strategies which maximize the potential of IT for the academic community, for the students and for their future employers?